The Role of Non-Performing Loan in Affecting Return on Assets at Perumda BPR Garut - Nurhayati, Dini; Kulsum, Imas Siti Umi (Golden Ratio of Data in Summary, 2023)
Perumda BPR Garut as a microfinance institution has a big challenge in managing non-performing loans (NPL), which can affect their financial performance. This study aims to analyse the effect of NPL on Return on Assets (ROA) at Perumda BPR Garut. The type of research used is quantitative research with a descriptive approach and simple regression analysis. The population of this study is the financial data of Perumda BPR Garut in the period 2018-2023, with samples taken using purposive sampling technique, consisting of six years of financial data. This research was conducted at Perumda BPR Garut, focusing on the relationship between NPL and ROA. The results show that NPL has a negative effect on ROA, which indicates that an increase in the number of non-performing loans will reduce the level of bank profitability. On the other hand, total assets are found to have a positive effect on ROA, which indicates that larger assets can improve the bank's financial performance. This study provides important implications regarding credit risk management, where a reduction in NPLs can improve ROA, which in turn contributes to better financial performance.